5×2+13=73

Subtract 13 from both sides of the equation.

5×2=73-13

Subtract 13 from 73.

5×2=60

5×2=60

Divide each term in 5×2=60 by 5.

5×25=605

Cancel the common factor of 5.

Cancel the common factor.

5×25=605

Divide x2 by 1.

x2=605

x2=605

Divide 60 by 5.

x2=12

x2=12

Take the square root of both sides of the equation to eliminate the exponent on the left side.

x=±12

Simplify the right side of the equation.

Rewrite 12 as 22⋅3.

Factor 4 out of 12.

x=±4(3)

Rewrite 4 as 22.

x=±22⋅3

x=±22⋅3

Pull terms out from under the radical.

x=±23

x=±23

The complete solution is the result of both the positive and negative portions of the solution.

First, use the positive value of the ± to find the first solution.

x=23

Next, use the negative value of the ± to find the second solution.

x=-23

The complete solution is the result of both the positive and negative portions of the solution.

x=23,-23

x=23,-23

x=23,-23

The result can be shown in multiple forms.

Exact Form:

x=23,-23

Decimal Form:

x=3.46410161…,-3.46410161…

Solve using the Square Root Property 5x^2+13=73